2000
DOI: 10.2337/diacare.23.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake and incidence of type 2 diabetes in men.

Abstract: R E S U LT S -T h e re were 149 incident cases of type 2 diabetes during 52,588 person-years of follow-up. There was a U-shaped association between alcohol intake and diabetes, with the lowest incidence of diabetes at Q2 (61.9-122.7 g/week). As compared with Q2, men in Q3 and Q4 had a 2.2-(95% CI 1.2-3.9, P = 0.01) and 2.4-fold (1.4-4.4, P 0.01) risk of developing diabetes, while nondrinkers and men in Q1 had 1.8-(1.0-3.3, P 0.05) and 1.4-fold (0.7-2.6, P = 0.34) higher risk of diabetes, re s p e c t i v e l y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
149
2
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(164 citation statements)
references
References 5 publications
8
149
2
5
Order By: Relevance
“…Fasting hyperglycemia was found in 3160 men (11.0% of men; currently taking drugs for DM: 1.8%, fasting plasma glucose Z7.0 mmol/l: 2.6%; fasting plasma glucose 6.1-6.9 mmol/l: 6.6%) and 2725 women (8.3% of women; currently taking drugs for DM: 1.9%, fasting plasma glucose Z7.0 mmol/l: 2.0%; fasting plasma glucose 6.1-6.9 mmol/l: 4.4%). The mean BMI, WHR, and WC for men were 23 20 3.5% of men and 3.3% of women were obese (Z30) and 29.7% of men and 18.0% of women were overweight (Z25). Using the WHO cutoffs for WHR, 20 2.1% of men (Z1.0) and 12.5% of women (Z0.85) had central obesity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fasting hyperglycemia was found in 3160 men (11.0% of men; currently taking drugs for DM: 1.8%, fasting plasma glucose Z7.0 mmol/l: 2.6%; fasting plasma glucose 6.1-6.9 mmol/l: 6.6%) and 2725 women (8.3% of women; currently taking drugs for DM: 1.9%, fasting plasma glucose Z7.0 mmol/l: 2.0%; fasting plasma glucose 6.1-6.9 mmol/l: 4.4%). The mean BMI, WHR, and WC for men were 23 20 3.5% of men and 3.3% of women were obese (Z30) and 29.7% of men and 18.0% of women were overweight (Z25). Using the WHO cutoffs for WHR, 20 2.1% of men (Z1.0) and 12.5% of women (Z0.85) had central obesity.…”
Section: Resultsmentioning
confidence: 99%
“…16 Several studies in the US and England have indicated that smoking and alcohol consumption are associated with diabetes. [23][24][25] Smoking and drinking may increase the risk of diabetes through their effects on obesity or through physiological factors. 26,27 Few studies have compared the degree of association of BMI, WC, and WHR with hyperglycemia after adjustment for age and the use of cigarettes and alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been no prospective studies evaluating the effect of long-term alcohol use on insulin sensitivity, per se, there have been a number of studies investigating whether there is any association between alcohol use at baseline and subsequent incidence of type 2 diabetes. Many of these studies found that light (ϳ3-18 g/day) (11)(12)(13) to moderate (18 -49 g/day) (14 -16) alcohol use was associated with a reduced risk for the development of diabetes. Two of these studies (11,13) were hampered due to the very limited number of subjects with moderate to heavy intake (i.e., Ͼ20 g/day, equivalent to more than two standard drinks per day).…”
mentioning
confidence: 99%
“…The meta-analysis done by Landol J Koppes 11 suggested that there is no reduction in the risk of Diabetes mellitus in heavy drinkers. Some of the studies have shown a non-linear relationship, [11][12][13][14] suggesting that moderate alcohol consumers may have reduced risk of Type-II DM as compared to the abstainers. However, even these studies agree that high alcohol consumption may increase the risk of Type-II DM.…”
Section: Resultsmentioning
confidence: 99%